Conceitos e propriedades de funções sob a ótica do ensino básico - Silvestre, Adriane Lemes (2016)
This study presents a proposal for teaching support materials to work with the beginning of the Function content in the first year of high school. Starting from the exhibition of the Function concept addressed in different bibliographies and then develop the content through of properties and examples involving, in particular, bijectivity, composition and inversion of functions. Ended with function transformations of graphics general functions.